Retirement provident fund and future of BPO sector in Bangladesh: a case study on Data-Path Limited - Khan, Nafees Imtiaz (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.